2010
DOI: 10.1007/s10528-010-9338-z
|View full text |Cite
|
Sign up to set email alerts
|

AFLP-Based Genetic Diversity Assessment of Commercially Important Tea Germplasm in India

Abstract: India has a large repository of important tea accessions and, therefore, plays a major role in improving production and quality of tea across the world. Using seven AFLP primer combinations, we analyzed 123 commercially important tea accessions representing major populations in India. The overall genetic similarity recorded was 51%. No significant differences were recorded in average genetic similarity among tea populations cultivated in various geographic regions (northwest 0.60, northeast and south both 0.59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Further, high level of hetozygosity (av Ho 0.775; He 0.847) revealed by SSR markers analysis suggested high level of out crossing in tea. These results are congruent with previous AFLP analysis of selected tea collections from western Himalaya (Karthigeyan et al, 2008;Sharma et al, 2010). Present SSR analysis revealed that China/China hybrids and Assam accessions shared 22 % average GS.…”
Section: (Tugms12)supporting
confidence: 92%
See 2 more Smart Citations
“…Further, high level of hetozygosity (av Ho 0.775; He 0.847) revealed by SSR markers analysis suggested high level of out crossing in tea. These results are congruent with previous AFLP analysis of selected tea collections from western Himalaya (Karthigeyan et al, 2008;Sharma et al, 2010). Present SSR analysis revealed that China/China hybrids and Assam accessions shared 22 % average GS.…”
Section: (Tugms12)supporting
confidence: 92%
“…Related C. japonica was clustered as a solitary out-group. Interestingly, single accessions from (CSIN303536) was grouped with China/China hybrids from western Himalayan region as earlier reported in AFLP analysis (Sharma et al, 2010). Further, SSR markers used in this study could differentiate each one of China/China hybrids and Assam types in spite of the high degree of similarity in morphology and geographical locations.…”
Section: Genetic Similarity and Cluster Analysissupporting
confidence: 75%
See 1 more Smart Citation
“…Molecular marker have proven to be a powerful approach for the study of genetic variation, relationships, molecular identification, and phylogeny of different cultivars, as well as for cultivar discrimination and fingerprinting of plant species (Boczkowska et al, 2012;Frascaroli et al, 2013;El-Esawi et al, 2016;Lassois et al, 2016). The different types of molecular markers such as random amplification of polymorphic DNA (RAPD) (Arakawa et al, 2016), restriction fragment length polymorphism (RFLP), inter simple sequence repeats (ISSR) (Devarumath et al, 2002;Liu et al, 2015), amplified fragment length polymorphism (AFLP) (Sharma et al, 2010;Ji et al, 2012), single nucleotide polymorphism (SNP) , and microsatellites or simple sequence repeats (SSR) (Taniguchi et al, 2014;Liu et al, 2017) have already been used for genetic and genomic analysis in tea plants. Of these approaches, SSR has become an important technique used in tea plant genetics and breeding for its multi-allelic nature, codominant inheritance, relative abundance, extensive genome coverage and simple detection (Zhao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, evaluation of the existing germplasm using different biochemical parameters that affect tea quality is an important method for selecting valuable germplasm. In recent years, numerous studies aiming to evaluate the germplasm resources of tea plants have also been conducted by incorporating various methods, including morphology, biochemistry and the use of genetic markers, such as random amplified polymorphic DNAs, restriction fragment length polymorphisms, inter‐simple sequence repeats and amplified fragment length polymorphisms, amongst others. Indeed, phenotypes can be referred to as rough standards for the evaluation of tea germplasms.…”
Section: Introductionmentioning
confidence: 99%